Luke's unique parables: Genesis narratives and interpretations of Jesus - Carmichael, Calum M. (Cambridge University Press, 2025)
Calum Carmichael presents a new perspective on how parables unique to Luke's Gospel were composed. These parables took up moral issues that arose out of conflicts among figures such as Jacob and Esau, Joseph and his brothers, Judah and Tamar as portrayed in Genesis narratives. Providing literary and linguistic analyses, Carmichael demonstrates how Luke, like many of his contemporaries, absorbed the narrative legacy of the Hebrew Bible and used it to express ideas about Jesus. The Joseph story was of particular interest to Luke because Joseph's role during the Egyptian famine resulted in the rescue of his family, thereby giving the Israelite nation a future. Carmichael's radically different approach identifies the influence of ancestral wrongdoing on how Luke portrayed Jesus' moral teaching.